Changes in Vitamin A Levels and the Effect of Early Vitamin A Supplementation on Vitamin A Levels in Infants Throughout the First 6 Months of Life: A Prospective Cohort Study in Chongqing, China - Liu, Huan; Chen, Qixiong; Yu, Linchao; Yang, Ting; Chen, Jie; Miao, Jingkun; Li, Tingyu (Frontiers in Public Health, 2021)
Objectives: This study aimed to explore the changes of infant VA status and effect of early VA supplementation on VA levels throughout the first 6 months of life. Methods: A prospective cohort study was conducted in Chongqing, China. 1016 healthy infants were enrolled at birth. Then, 930, 882, 854 and 822 healthy infants were followed up at postnatal 7 days, 1 month, 3 months and 6 months, respectively. Blood sample and data from dietary survey and physical development were collected. Serum VA was measured by chromatography tandem-mass spectrometry and was classified by the criteria of elder children aged 6-70 months (<0.70, 0.70–1.05, ≥1.05 µmol/L). Changes of VA status over age and the relationship of VA supplement with VA levels were investigated by generalized estimating equations. Results: Infant VA concentrations increased significantly from 0.499±0.146 to 1.061±0.414 µmol/L with age in 6 months, even without VA supplements (P<0.05). From birth to 6 months, the rate of VA <0.70 µmol/L decreased from 88.6% to 19.5%. During follow-up, no infant had clinical VA deficiency (VAD) conditions, such as night blindness, conjunctival xerosis or Bitot’s spot. And less than 7.0% of infants were underdeveloped for weight, length and head circumference.VA level of infants with VA≥0.588 µmol/L at birth gradually increased to adequate VA (VA≥1.05 µmol/L) at 6 months. For these infants, there was no significant difference in VA level between VA supplement and non-supplement groups (P>0.05). Infants with VA<0.430 µmol/L at birth still had VA<0.70 µmol/L at 6 months, whose VA levels increased by 0.08 µmol/L in supplement group than non-supplement group (P<0.05). Conclusions: The low VA levels of neonates at birth may be a normal physiological state for them and this physiological level increased with age. Not all neonates may need early VA supplementation. More multicentre studies are needed to explore the new cut-off point for diagnosis of neonatal VAD and nutritional interventions.